The membrane glycoprotein encoded by the retroviral oncogene v-erb-B is structurally related to tyrosine-specific protein kinases. - Privalsky, M L (1984)
Avian erythroblastosis virus can transform both fibroblasts and erythroid cells to neoplastic growth. A locus within the virus genome, v-erb B, encodes a membrane glycoprotein essential for the oncogenic properties of the virus. No biochemical function has until now been attributed to the v-erb B protein. We report here that the v-erb B glycoprotein shares strong structural homologies with the tyrosine-specific protein kinases encoded by certain retroviral oncogenes. The patterns of amino acid conservation between the tyrosine-specific protein kinases and the v-erb B protein, and between the v-erb B protein and the catalytic subunit of bovine protein kinase, suggest a possible functional as well as structural relatedness.